The Importance of Alexithymia in Post-surgery. Differences on Body Image and Psychological Adjustment in Breast Cancer Patients - Gutiérrez Hermoso, Lorena; Velasco Furlong, Lilian; Sánchez-Román, Sofía; Salas Costumero, Lorena (Frontiers in Psychology, 2020)
Breast cancer is a disease that is difficult to face and that often hinders body acceptance. Body changes due to surgery can be very emotionally challenging for those who experience them. The aim of this study is to explore the differences on body image and psychological adjustment on women with breast cancer with high and low alexithymia according to the type of surgery. In this cross-sectional study, 119 women diagnosed with breast cancer (stages I, II and III) were evaluated with different self-report questionnaires. Afterwards, patients were divided into two groups (high and low levels of alexithymia) to analyze dependent variables (body image and psychological adjustment) according to the type of surgery (radical mastectomy or breast conserving therapy). The results of the General Linear Model suggest that when patients show high alexithymia combined with having undergone a radical mastectomy, they show higher levels of Hopelessness. Furthermore, in patients with high alexithymia, higher scores of maladaptive coping styles and greater distortion of body image were found. Alexithymia seems to play an important role in the way in which women cope with their disease, especially in those with radical mastectomy.